2016
DOI: 10.1016/j.chom.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpu Mediates HLA-C Downregulation

Abstract: SUMMARY Many pathogens evade cytotoxic T lymphocytes (CTLs) by downregulating HLA molecules on infected cells, but the loss of HLA can trigger NK cell-mediated lysis. HIV-1 is thought to subvert CTLs while preserving NK cell inhibition by Nef-mediated downregulation of HLA-A and -B but not HLA-C molecules. We find that HLA-C is downregulated by most primary HIV-1 clones, including transmitted founder viruses, in contrast to the laboratory-adapted NL4-3 virus. HLA-C reduction is mediated by viral Vpu and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
161
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(170 citation statements)
references
References 71 publications
8
161
1
Order By: Relevance
“…This raises the possibility that cells infected with viruses encoding wild-type Nef are protected from NK cell-mediated ADCC by their incapacity to ligate sufficient activating receptors and capacity to ligate sufficient inhibitory NK cell receptors to generate a cumulative inhibitory NK cell signal. Indeed, previous research has demonstrated that HIV-1-infected targets express sufficient HLA-C and HLA-E to inhibit anti-HIV-1 ADCC (14,15) despite the ability of primary Vpu to downregulate HLA-C to various extents (38). Given that cumulative signals are important determinants of ADCC susceptibility, future research should assess if target cells infected with viruses coding for wild-type Nef become susceptible to ADCC after blockade of inhibitory NK cell receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that cells infected with viruses encoding wild-type Nef are protected from NK cell-mediated ADCC by their incapacity to ligate sufficient activating receptors and capacity to ligate sufficient inhibitory NK cell receptors to generate a cumulative inhibitory NK cell signal. Indeed, previous research has demonstrated that HIV-1-infected targets express sufficient HLA-C and HLA-E to inhibit anti-HIV-1 ADCC (14,15) despite the ability of primary Vpu to downregulate HLA-C to various extents (38). Given that cumulative signals are important determinants of ADCC susceptibility, future research should assess if target cells infected with viruses coding for wild-type Nef become susceptible to ADCC after blockade of inhibitory NK cell receptors.…”
Section: Discussionmentioning
confidence: 99%
“…HIV ‐1 down‐regulates HLA class I expression on the surface of infected CD 4 + T cells so as to evade CD 8 + T‐cell lysis 86, 87. However, this action exposes the infected cells to recognition and lysis by natural killer ( NK ) cells through KIR s. The effectiveness of an NK cell response, and consequently the outcome of infection, are linked to the host's KIR genes, their copy number and the expression levels of their ligands.…”
Section: Kir Geneticsmentioning
confidence: 99%
“…Unlike HLA-A and HLA-B alleles, the surface expression level of HLA-C alleles is not down-regulated by Nef and therefore HLA-C may be relatively stable after HIV-1 infection (Cohen et al, 1999; Le Gall et al, 1998). However, a recent study demonstrated that some HIV strains are able to down-modulate HLA-C on the infected cell surface by Vpu (Apps et al, 2016). Thus, binding between peptide-HLA-C complex and KIR2D, which is sensitive to sequence variation of the bound peptide, might be key in regulating the activity of NK cells (Alter et al, 2011; Fadda et al, 2012; Thananchai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%